2015
DOI: 10.1088/0004-637x/801/1/69
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Spurious Iron Spread in the Globular Cluster NGC 3201

Abstract: NGC 3201 is a globular cluster suspected to have an intrinsic spread in the iron content. We re-analysed a sample of 21 cluster stars observed with UVES-FLAMES at the Very Large Telescope and for which Simmerer et al. found a 0.4 dex wide [Fe/H] distribution with a metal-poor tail. We confirmed that when spectroscopic gravities are adopted, the derived [Fe/H] distribution spans ∼0.4 dex. On the other hand, when photometric gravities are used, the metallicity distribution from Fe I lines remains large, while th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 51 publications
8
62
0
Order By: Relevance
“…These differences are comparable to the internal precision of our measurements. A similar but possibly relevant issue related to differences in [Fe/ H] derived from 1D LTE analyses of RGB, as opposed to AGB, stars has been noted by Ivans et al (2001;NGC 5904), Lapenna et al (2014;NGC 104), and Mucciarelli et al (2015;NGC 3201). These authors found that the derived [Fe I/H] abundances were ∼0.10-0.15 dex lower than the [Fe II/H] abundances for AGB, but not RGB, stars when the model atmosphere parameters were determined via spectroscopic methods.…”
Section: Model Atmospheresmentioning
confidence: 67%
“…These differences are comparable to the internal precision of our measurements. A similar but possibly relevant issue related to differences in [Fe/ H] derived from 1D LTE analyses of RGB, as opposed to AGB, stars has been noted by Ivans et al (2001;NGC 5904), Lapenna et al (2014;NGC 104), and Mucciarelli et al (2015;NGC 3201). These authors found that the derived [Fe I/H] abundances were ∼0.10-0.15 dex lower than the [Fe II/H] abundances for AGB, but not RGB, stars when the model atmosphere parameters were determined via spectroscopic methods.…”
Section: Model Atmospheresmentioning
confidence: 67%
“…and M22 (Pilachowski et al 1982;Da Costa et al 2009;Marino et al 2009Marino et al , 2011b, may host multiple populations with distinct [Fe/H] ratios. However, recent studies by Mucciarelli et al (2015b) and Lardo et al (2016) Lapenna et al (2014), and Mucciarelli et al (2015c) found that [Fe/H] determinations for RGB and AGB stars can differ systematically by >0.1 dex, and that mixing RGB and AGB stars in a sample can produce an artificial metallicity spread. A common thread connecting these issues is the method by which a star's surface gravity is determined (spectroscopic versus photometric).…”
Section: Metallicity Distributionmentioning
confidence: 98%
“…For example, Figure 6 shows that NGC 6229 has significantly lower [Na/Fe] 8 We note that Simmerer et al (2013) found a potential [Fe/H] spread in NGC 3201, and that the cluster has a fainter absolute magnitude than NGC 6229 with M V = -7.45 (Harris 1996). However, Mucciarelli et al (2015) Carretta et al (2009b,c), and represent the general trends exhibited by ∼15 monometallic clusters. The cyan symbols represent the abundance trends of several clusters (filled symbols) and field stars (open circles) associated with the Sagittarius dwarf spheroidal galaxy (Bonifacio et al 2000;Cohen 2004;Sbordone et al 2007;Carretta et al 2010a;McWilliam et al 2013;Carretta et al 2014bCarretta et al , 2017.…”
Section: Implications Of Correlated Light and Heavy Element Abundancementioning
confidence: 78%